Taxes and corporate borrowing: Empirical evidence from selected african countries. - Abor, J.; Bokpin, G.A.; Fiawoyife, E. (My University, 2011)
In this study the authors examine the effect of taxes on corporate borrowing in selected African countries. With use of a panel regression model, their results suggest that taxation is not important in explaining corporate borrowing decisions. However, they found significant relationships between the other firm-level characteristics and debt-equity ratio. Firm age, for instance, shows a negative effect on debt-equity ratio in Ghana and Kenya but registers a positive effect on debt-equity ratio in South Africa. Firm size signals a positive effect on debt-equity ratio in Kenya and South Africa. Also, debt-equity ratio is negatively affected by profitability in Kenya and growth potential in Nigeria.
Keywords: Africa, corporate borrowing, taxes